Evaluasi Sinkronisasi Program Pemanfaatan Ruang RTRW Terhadap RPJMD Kabupaten Lampung Utara Tahun 2020-2024 - Runiawan, Aken Andha; Endaryanto , Teguh; Yuliawan , Dedy (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
This study aims to evaluate the synchronization of the medium-term spatial utilization program in the Regional Spatial Planning (RTRW) of North Lampung Regency with the Regional Medium-Term Development Plan (RPJMD) of North Lampung Regency for the 2020-2024 period. The research method uses descriptive analysis and synchronization analysis of the five-year medium-term spatial utilization program with secondary data from the planning documents of the North Lampung Regency Government. The results indicate that the synchronization level of the medium-term RTRW program with the RPJMD during this period is relatively low, with 42% of the programs experiencing suboptimal synchronization. The primary causes of this low synchronization are the lack of socialization and the limited involvement of implementing agencies in the drafting process of spatial planning and development documents. Policies that can be implemented by the Government of North Lampung Regency to improve this synchronization include conducting training for employees related to SPPR and providing an understanding of SPPR to regional heads.